2011
DOI: 10.1038/modpathol.2011.113
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating neutrophils in pancreatic neoplasia

Abstract: The interaction between tumor cells and inflammatory cells has an important role in cancer initiation and progression; however, this interaction has not been systematically investigated in pancreatic neoplasia. In this study, the presence of tumor-infiltrating neutrophils within and/or adjacent to neoplastic cells was investigated in pancreatic neoplasms. Areas with >10 tumor-infiltrating neutrophils/100 epithelial cells were arbitrarily classified as positive. Those with 11–15 tumor-infiltrating neutrophils w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
120
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 26 publications
5
120
0
Order By: Relevance
“…32 Similarly, infiltration of gliomas by neutrophils has been correlated with higher tumor stages 33 and it is apparently also associated with more aggressive types of pancreas carcinomas. 34 In accordance, tumor infiltrating neutrophils represent a highly potent therapeutic target. Thus, to understand the physiology of tumor infiltrating neutrophils is of utmost importance.…”
Section: Discussionmentioning
confidence: 98%
“…32 Similarly, infiltration of gliomas by neutrophils has been correlated with higher tumor stages 33 and it is apparently also associated with more aggressive types of pancreas carcinomas. 34 In accordance, tumor infiltrating neutrophils represent a highly potent therapeutic target. Thus, to understand the physiology of tumor infiltrating neutrophils is of utmost importance.…”
Section: Discussionmentioning
confidence: 98%
“…However, neutrophils are also actively recruited into the tumor microenvironment in both cancer patients and mouse models of cancer. In humans, intratumoral infiltration of neutrophils has been detected in gastric carcinoma [200][201][202], bronchioloalveolar carcinoma [170,203], non-small cell lung carcinoma [204], pancreatic neoplasia [205], pancreatic ductal adenocarcinoma [206], bladder cancer [147], glioma [207], cervical carcinoma [139] and breast carcinoma [4,208] ( Table 1). The clinical consequences of intratumoral and circulating neutrophils in cancer patients will be discussed in "Prognostic Values of Neutrophils and Other Myeloid Subtypes in Cancer Patients" section.…”
Section: Neutrophil Recruitment To the Tumor Microenvironmentmentioning
confidence: 99%
“…Another study showed that pancreatic adenocarcinoma-infiltrating γδ-T cells are a highly influential lymphocyte subset promoting pancreatic oncogenesis and reducing survival via novel cross-talk with the adaptive immune compartment; Nevertheless, they may also have prognostic significance of survival and response to immunotherapeutic regimen (77). Investigators from our Institution have reported an association between tumorassociated neutrophils (TANs) and advanced IPMN lesions (78). The recent publication of Gemenetzis et al (79) evaluating the correlation between NLR and platelet-tolymphocyte ratio (PLR) values and the presence of invasive carcinoma in patients with IPMN.…”
Section: Peripheral Blood Cellmentioning
confidence: 99%